Chemistry of Lipid A: At the Heart of Innate Immunity - Molinaro, Antonio; Holst, Otto; Di Lorenzo, Flaviana; Callaghan, Maire; Nurisso, Alessandra; D'Errico, Gerardino; Zamyatina, Alla; Peri, Francesco; Berisio, Rita; Jerala, Roman; Jiménez-Barbero, Jesús; Silipo, Alba; et al. (Chemistry : a European journal, 2015)
In many Gram‐negative bacteria, lipopolysaccharide (LPS) and its lipid A moiety are pivotal for bacterial survival. Depending on its structure, lipid A carries the toxic properties of the LPS and acts as a potent elicitor of the host innate immune system via the Toll‐like receptor 4/myeloid differentiation factor 2 (TLR4/MD‐2) receptor complex. It often causes a wide variety of biological effects ranging from a remarkable enhancement of the resistance to the infection to an uncontrolled and massive immune response resulting in sepsis and septic shock. Since the bioactivity of lipid A is strongly influenced by its primary structure, a broad range of chemical syntheses of lipid A derivatives have made an enormous contribution to the characterization of lipid A bioactivity, providing novel pharmacological targets for the development of new biomedical therapies. Here, we describe and discuss the chemical aspects regarding lipid A and its role in innate immunity, from the (bio)synthesis, isolation and characterization to the molecular recognition at the atomic level. Pivotal understanding: The chemical and biochemical aspects of lipid A, the endotoxic moiety of the bacterial lipopolysaccharide (LPS) molecule is discussed, as well as its role in innate immunity, from the (bio)synthesis, isolation and characterization to the molecular recognition at the atomic level, which helps to understand the bioactivity of LPS.